Non-invasive detection of exercise-induced cardiac conduction abnormalities in sudden cardiac death survivors in the inherited cardiac conditions. Issue 2 (21st October 2020) - Leong, Kevin Ming Wei; Ng, Fu Siong; Shun-Shin, Matthew J; Koa-Wing, Michael; Qureshi, Norman; Whinnett, Zachary I; Linton, Nick F; Lefroy, David; Francis, Darrel P; Harding, Sian E; Davies, D Wyn; Peter, Nicholas S; et al.
Abstract: Aims : Rate adaptation of the action potential ensures spatial heterogeneities in conduction across the myocardium are minimized at different heart rates providing a protective mechanism against ventricular fibrillation (VF) and sudden cardiac death (SCD), which can be quantified by the ventricular conduction stability (V-CoS) test previously described. We tested the hypothesis that patients with a history of aborted SCD due to an underlying channelopathy or cardiomyopathy have a reduced capacity to maintain uniform activation following exercise. Methods and results : Sixty individuals, with ( n  = 28) and without ( n  = 32) previous aborted-SCD event underwent electro-cardiographic imaging recordings following exercise treadmill test. These included 25 Brugada syndrome, 13 hypertrophic cardiomyopathy, 12 idiopathic VF, and 10 healthy controls. Data were inputted into the V-CoS programme to calculate a V-CoS score that indicate the percentage of ventricle that showed no significant change in ventricular activation, with a lower score indicating the development of greater conduction heterogeneity. The SCD group, compared to those without, had a lower median (interquartile range) V-CoS score at peak exertion [92.8% (89.8–96.3%) vs. 97.3% (94.9–99.1%); P  < 0.01] and 2 min into recovery [95.2% (91.1–97.2%) vs. 98.9% (96.9–99.5%); P  < 0.01]. No significant difference was observable later into recovery at 5 or 10 min. Using the lowest median V-CoS scores obtained during the entire recovery period post-exertion, SCD survivors had a significantly lower score than those without for each of the different underlying aetiologies. Conclusion : Data from this pilot study demonstrate the potential use of this technique in risk stratification for the inherited cardiac conditions.